2018
DOI: 10.25165/j.ijabe.20181105.3544
|View full text |Cite
|
Sign up to set email alerts
|

Design and experiment of multi-row pneumatic precision metering device for rapeseed

Abstract: The main objective of this study was to design a pneumatic disk with four-rows for planting rapeseed and to investigate its performance under several rotating speeds and vacuum pressure values. The effects of rotating speeds, vacuum pressure and rows on seed sucking and retaining were inspected. Six rotating speeds (5 r/min, 10 r/min, 15 r/min, 20 r/min, 25 r/min and 30 r/min) incorporated with the application of vacuum pressure were employed for detecting the optimum vacuum amount that was sufficient for seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
(10 reference statements)
3
9
0
Order By: Relevance
“…These results are in line with earlier studies where in general low damage rates are found [23,46], with an exception for dicots seed where splitting often results into damage rates above 10% [5,49]. Once more, pneumatic seeders are proposed to further reduce seed damage as fewer moving parts are assumed to produce friction with the grains [45,46], and while on occasion successful in doing so [50], seed damage is often not reported on [26,27,33]. Yet so, the potential benefits would not outweigh increased acquisition and maintenance costs for small-scale farm operations [25].…”
Section: Discussionsupporting
confidence: 88%
“…These results are in line with earlier studies where in general low damage rates are found [23,46], with an exception for dicots seed where splitting often results into damage rates above 10% [5,49]. Once more, pneumatic seeders are proposed to further reduce seed damage as fewer moving parts are assumed to produce friction with the grains [45,46], and while on occasion successful in doing so [50], seed damage is often not reported on [26,27,33]. Yet so, the potential benefits would not outweigh increased acquisition and maintenance costs for small-scale farm operations [25].…”
Section: Discussionsupporting
confidence: 88%
“…The purpose was to reduce the number of metering units per each planting machine, decrease pressure and power consumption, and simplifies power transmission and pressure systems construction, as well as reducing total planter manufacturing and operating cost. However, the two rows of holes closer to the plate center of rotation resulted in more multiple seed pick-up than the other two rows which stated in previous study carried out by some scholars [12]. These results returned mainly to the variation in linear velocities of the rows and comparatively higher vacuum pressure gathering around plate center of rotation.…”
Section: Introductionmentioning
confidence: 75%
“…The model was acceptably depicted vacuum pressure required by the planter with chi-square; root means square error and modeling efficiency of 2.51×10 -3 , 2.74×10 -2 and 0.99, respectively. [12] designed a multi-rows pneumatic plate for metering rapeseed. Through this endeavor they investigated the effect of metering plate speed, vacuum pressure and rows levels on device performance and developed a mathematical model for predicting of vacuum amount which matches the corresponding plate rotating speed.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were carried out on a laboratory bench in six iterations. At the same time, the vacuum capacity of the fan was 40 MB [6][7].In the experiments, the holes of the seeding machine disc were left open at intervals from 4 to 16 (table.1), the rest were closed.The experiments were carried out in the following order, depending on the width, length and thickness of the seed suction into the disc holes in the cross section [8][9][10].We explain the order by length according to the state of suction (figure 2). In Option 1 (figure 2), three pieces of pollen were tied to a thread with the ends pointing downwards.…”
Section: Methodsmentioning
confidence: 99%